THE ELEMINASI GANGGUAN KOGNITIF DENGAN INTERVENSI GIZI DAN INTERVENSI TERAPI PADA LANSIA DI PROVINSI NTT - Lina Yunita (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
The rapidly growing number of elderly people in NTT and dementia provinces is the most common cause of cognitive problems which are a major public health problem in the elderly. Nutrition plays a role in the aging process, but still lacks knowledge about the risk factors associated with nutrition in cognitive diseases. Research in this field evolved over the last period and resulted in subclinical deficiencies in important nutrients (antioxidants such as vitamins C, E and b-carotene, vitamin B12, vitamin B6, folate) and related related nutrients, such as hypercholesterolemia, hypriacylglyceremia, hypertension, and diabetes can cause several factors related to nutrition before increasing cognitive problems. The purpose of this discussion is to see a picture that becomes a factor that gave rise to cognitive theory, nutrition in the elderly and stimulation provided based on relevant studies. The method used uses secondary data conversion that is verified and assessed for a significant assessment of the specific cognitive assessment of dementia in old age and nutritional factors that can inhibit the incidence of dementia. Some therapies are used to protect cognitive elderly with brain gymnastic therapy, group stimulation therapy (TSK) and music therapy. These three therapies are important for preventing cognitive elderly. Drug therapy for Alzheimer's cognitive disease does not yet exist, need risk factors for cognitive impairment need to be early and not continued in the aging process.